A conceptual framework for cloud-based integration of Virtual laboratories as a multi-agent system approach. (December 2016) - Erdem, Mehmet Bilgehan; Kiraz, Alper; Eski, Hüseyin; Çiftçi, Özgür; Kubat, Cemalettin
Highlights: A conceptual model is designed for gathering all Virtual Labs in a common base. Multi-agent based integrated Virtual Labs management system is proposed. Possible interactions between Virtual Labs are introduced. This model will help to relax Virtual Labs' boundary problems. This study can give useful insights to the Virtual Lab researchers. Abstract: With the rapid development in information technologies, numerous Virtual laboratory (VL) studies are being conducted in various fields such as material science, computer science, chemistry and education. While the number of VL studies are rising, possible interactions between these VLs have not been studied yet. The aim of this study is to create a framework in order to gather all VLs in a common base by building interactions between VLs via a multi-agent system (MAS) approach. Cloud-Based Integrated Virtual Laboratories (CIVIL) model has been proposed as a conceptual framework of collaborative networks of a cloud system with the help of MAS. The boundaries of the integrated problem are determined and schematized within the scope of conceptual modeling. Thereafter probable entities that may interact in the framework are included in the MAS model. Communications and interactions between these entities, aims and performance indicators of defined agents are also listed.